Stress : concepts, cognition, emotion, and behavior - Fink, George (Boston ; Academic Press, an imprint of Elsevier, 2016)
"Stress: Concepts, Cognition, Emotion, and Behavior: Handbook in Stress Series, Volume 1, examines stress and its management in the workplace and is targeted at scientific and clinical researchers in biomedicine, psychology, and some aspects of the social sciences. The audience is appropriate faculty and graduate and undergraduate students interested in stress and its consequences. The format allows access to specific self-contained stress subsections without the need to purchase the whole nine volume Stress handbook series."- www stránky vydavatele
Keywords: stres (psychologie); stres (fyziologie); stres z povolání; stress (psychology); stress (physiology); occupational stress; sborníky; papers of several authors